Edgar Degas - Self Portrait - 1855 - Edgar Degas (NC, 2026)
Courtesy of the Musée d'Orsay, Paris.
Droits : Licence indiquee par Wikimedia Commons
Keywords: Degas; Peintures; Musée; musée; musée national; Peintures